Balancing professional obligations and risks to providers in learning healthcare systems. Issue 6 (27th March 2020) - Piasecki, Jan; Dranseika, Vilius
Abstract : Clinicians and administrators have a professional obligation to contribute (OTC) to improvement of healthcare quality. At the same time, participation in embedded research poses risks to healthcare institutions. Disclosure of an institution's sensitive information could endanger relationships with patients and undermine its reputation. The existing ethical framework (EF) for learning healthcare systems (LHSs) does not address the conflict between the OTC and institutional interests. Ethical guidance and policy regulation are needed to create a safe environment for embedded research. In this article we analyse the EF for LHSs and the concept of professionalism. We suggest that the EF should be supplemented with an obligation to protect provider's legitimate interests. We define legitimate interests as those that enable providers to discharge their primary duties. We argue that both the OTC and the obligation to protect legitimate interests are grounded in the concept of medical professionalism and can be understood as a matter of contract between a democratic society and medical professionals. The proposed supplemented EF can be implemented into a regulatory system in three different ways: the self-regulating : where providers decide themselves how to balance the ethical claims, the centralised: where a governmental institution decides the right balance between providers' interests and interests of a health system; and the mediating : where medical professionals, the state and patients negotiate their interests. Our article contributes to the discussion on ethical relevance of providers' interests and the regulatory model for weighing opposite interests in LHSs.